(untitled) - Kerlinger, Fred N. (New York, 1986)
First published in 1964, this text has set the standard for other texts in the field of behavioral research methodology. It emphasises the fundamentals of understanding how to solve a scientific research problem, focusing upon the relationship between the research problems and the design of the research. This edition has more examples from psychology, sociology, and education than the previous edition and places a greater emphasis on multivariate approaches and methods
Keywords: Psychology,Sociology,Psychology,Sociology,Tâm lý học,Xã hội học,Tâm lý học,Xã hội học; Research,Research,Statistical methods,Statistical methods,Nghiên cứu,Nghiên cứu,Điều tra xã hội,Điều tra xã hội